Accessibility and utility of library resources in research methodology course: A case of non-science students at the University of Malaya - Azman, Muhammad Danial; Hamidi, Mashitah; Ong, Siew Kian (Malaysian Journal of Library and Information Science, 2018)
This paper investigates the accessibility and utility of library resources when studying research methodology among the non-science students at the University of Malaya Kuala Lumpur. It addresses the primary concerns of accessibility and utility among students when engaging library resources and undertaking the core subject “Research Methodology” both at the faculty level, as well as at three departments under the Faculty of Arts and Social Sciences. In doing so, survey questionnaires were distributed among students doing research methodology across three distinct yet interrelated subfields of the Arts and Social Sciences, namely Anthropology and Sociology, Chinese Studies, and International and Strategic Studies. This descriptive study employs both quantitative and qualitative data gathering techniques through: (a) survey captured through an email invitation to a specific target of undergraduate and postgraduate students who have completed their research methodology course; (b) a focus group discussion (FGD) conducted to discuss students’ responses toward initial findings from the surveys. The findings indicate that despite the pivotal role played by the library in facilitating the learning of research method, there is greater need to recognise the specific needs of library resources in research methodology in Arts, Humanities and Social Sciences. This should be able to help the acquisition division of respective university libraries in their future planning, particularly given the variety and diversity of research traditions in the non-science discipline.